(untitled) (Hematology Meeting Reports, 2009)
Angiogenesis is essential for tumor growth and metastasis formation. Many agents have been developed to inhibit this process. Two major anti-angiogenic strategies have been so far mostly developed: the vascular endothelial growth factor (VEGF) monoclonal antibody bevacizumab and several tyrosine kinase inhibitors (TKI) to VEGF receptors. Bevacizumab is the first specific anti-angiogenic agent registered. This registration was based on the results of the phase III trial which compared first-line chemotherapy plus bevacizumab to chemotherapy alone in patients with metastatic colorectal cancer. Treatment with chemotherapy plus bevacizumab resulted in higher response rates (chemotherapy, 35%, chemotherapy plus bevacizumab, 45%) and longer median survival (chemotherapy, 15.6 months, chemotherapy plus bevacizumab, 20.3 months).1